1948
DOI: 10.1063/1.1746834
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Interaction between Starch and Iodine

Abstract: (1) It is postulated that the interaction between starch and iodine in the amylose-iodine complex is of dipolar nature. (2) A model for such dipolar interaction is proposed and the necessity for a cooperative effect is discussed. (3) The interaction energy is calculated as a function of a parameter x and it is shown that this parameter possesses a critical value at which a ``condensation'' of iodine into the complex occurs. (4) It is demonstrated that it is physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1951
1951
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…It is known that parts of the straight chains in the non-reducing termini of the amylopectin side chains form double helices (Kainuma and French, 1972). These helices are arranged in parallel composition with hydrogen bonding between adjoining glucose residues (Stein and Rundle, 1948). This is the basis of crystal formation in starch.…”
Section: Resultsmentioning
confidence: 98%
“…It is known that parts of the straight chains in the non-reducing termini of the amylopectin side chains form double helices (Kainuma and French, 1972). These helices are arranged in parallel composition with hydrogen bonding between adjoining glucose residues (Stein and Rundle, 1948). This is the basis of crystal formation in starch.…”
Section: Resultsmentioning
confidence: 98%
“…These results show that the rate of the formation of the PVA-iodine complex was smaller than that of the iodine sorption. It is well known that Young's modulus of a polymer gel, E, is expressed as a function of the volume fraction of the polymer, V,, as follows19-22: log E = log A + B log V, (6) where A and B are constants. Young's moduli of water-swollen PVA membranes are plotted against the volume fraction of polymer, V, = 1 -H,, in Figure 4, to show that eq.…”
Section: Changes In Volume and Modulus Due To Iodine Sorptionmentioning
confidence: 99%
“…More recently, Teitelbaum et al concluded that the major component of iodine in the amylose helix is in the form of I 5 from resonance Raman and iodine Mössbauer spectroscopies (Teitelbaum et al, 1978, Teitelbaum et al, 1980. As for the interaction in the complex, it is not resolved whether main contribution comes from dispersion force, or it originates from induced dipole in iodine molecules (Stein & Rundle, 1948), or there are charge transfer from amylose oxygen to iodine chains (Murakami, 1954).…”
Section: Introductionmentioning
confidence: 99%